Hubungan Antara Kepercayaan Diri Dan Dukungan Sosial Teman Sebaya Terhadap Tingkat Kecemasan Pada Wanita Menopause - Dilla - Rahwuni; Widya - Lestari; Bayhakky - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the relationship between self confidence and the peer social support with the level of anxiety of menopause women in Kelurahan Sidomulyo Barat Kecamatan Tampan Pekanbaru. The research used correlation descriptive method with cross sectional design. The sampling technique was cluster sampling with 103 respondents which were recruited based on inclusion criteria. Data collection tool in this research was a questionnaire that has been tested it’s validity and reliability. Then, data were analyzed by using Chi Square test. The results shown that the respondents with high self confidence experienced a moderate level of anxiety were 41 respondents (77,4%). Next, the research result also showed that menopausal women with high the peer social support experienced a moderate level of anxiety were 44 respondent (77,2%). The results of correlation test between self confindence and level of anxiety showed that p value = 0,000. It meant that there was a relationship between self confidence with the level of anxiety of menopause women. The results of correlation test between peer social support also showed that p value = 0,000. It meant that there was a relationship between self confidence with the level of anxiety of menopause women. The results of this research recommend public health center to form facility for a group mothers of menopause, like POSBINDU, so that mothers with menopause can share their opinions, knowledge, experience about menopause with others. Therefore, it can lowering the level of anxiety to menopause women. Keyword: Level of anxiety, menopause, peer social support, self confidence.